Microbial Shifts in the Intestinal Microbiota of Salmonella Infected Chickens in Response to Enrofloxacin - Li, Jun; Hao, Haihong; Cheng, Guyue; Liu, Chunbei; Ahmed, Saeed; Shabbir, Muhammad A. B.; Hussain, Hafiz I.; Dai, Menghong; Yuan, Zonghui (Frontiers in Microbiology, 2017)
Fluoroquinolones (FQs) are important antibiotics used for treatment of Salmonella infection in poultry in many countries. However, oral administration of fluoroquinolones may affect the composition and abundance of a number of bacterial taxa in the chicken intestine. Using 16S rRNA gene sequencing, the microbial shifts in the gut of Salmonella infected chickens in response to enrofloxacin treatments at different dosages (0, 0.1, 4 and 100 mg/kg b.w.) were quantitatively evaluated. The results showed that the shedding levels of Salmonella were significantly reduced in the high dosage group as demonstrated by both culturing method and 16S rRNA sequencing method. The average values of diversity indices were higher in the control group than in the medicated groups. NMDS analysis results showed that the microbial community of high dosage group was clearly separated from the other groups. In total, 25 genera were significantly enriched (including 6 abundant genera: Lactococcus, Bacillus, Burkholderia, Pseudomonas, Rhizobium and Acinetobacter) and 23 genera were significantly reduced in the medicated groups than in the control group for the treatment period, but these bacterial taxa recovered to normal levels after therapy withdrawal. Additionally, 5 genera were significantly reduced in both treatment and withdrawal periods (eg. Blautia and Anaerotruncus) and 23 genera (eg. Enterobacter and Clostridium) were significantly decreased only in the withdrawal period, indicating that these genera might be the potential targets for the fluoroquinolones antimicrobial effects. Specially, Enterococcus was significantly reduced under high dosage of enrofloxacin treatment, while significantly enriched in the withdrawal period, which was presumably due to the resistance selection. Predicted microbial functions associated with genetic information processing were significantly decreased in the high dosage group. Overall, enrofloxacin at a dosage of 100 mg/kg b.w. significantly altered the microbial community membership and structure, and microbial functions in the chicken intestine during the medication. This study fully investigates the chicken intestinal microbiota in response to enrofloxacin treatment and identifies potential targets against which the fluoroquinolones may have potent antimicrobial effects. These results provide insights into the effects of the usage of enrofloxacin on chicken and will aid in the prudent and rational use of antibiotics in poultry industry.